2021
DOI: 10.1016/j.matcom.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of a Graphene Field-Effect Transistors by means of Design of Experiments

Abstract: Graphene, due to its unique electronic structure favoring high carrier mobility, is considered a promising material for use in high-speed electronic devices in the post-silicon electronic era. For this reason, experimental research on graphene-based field-effect transistors (GFETs) has rapidly increased in the last years. However, despite the continuous progress in the optimization of such devices many critical issues remain to be solved such as their reproducibility and performance uniformity against possible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These temperature values were chosen considering the value of the glass transition temperature for the pure PLA declared by the manufacturer, which is expected around 333.15 K. Such value is also confirmed by differential scanning calorimetry (DSC) measurements performed by the authors and reported in Batakliev et al [ 38 ] An almost uniform discretization on four levels around this value is adopted. This is in light of a design of experiment (DoE) to be performed in future work with an approach already successfully applied in our previous studies [ 29 , 39 , 40 ]. This approach is particularly indicated in case of interest to statistically analyze the effect of some conditioning parameters on a selected performance function.…”
Section: Methodsmentioning
confidence: 99%
“…These temperature values were chosen considering the value of the glass transition temperature for the pure PLA declared by the manufacturer, which is expected around 333.15 K. Such value is also confirmed by differential scanning calorimetry (DSC) measurements performed by the authors and reported in Batakliev et al [ 38 ] An almost uniform discretization on four levels around this value is adopted. This is in light of a design of experiment (DoE) to be performed in future work with an approach already successfully applied in our previous studies [ 29 , 39 , 40 ]. This approach is particularly indicated in case of interest to statistically analyze the effect of some conditioning parameters on a selected performance function.…”
Section: Methodsmentioning
confidence: 99%
“…The unevenness of these parameters, thus, impairs the uniformity of the fabricated devices' high-frequency capabilities. In [57], it was observed that FETs based on nanowires and nanotubes are more robust to processrelated geometry variations as compared to bulk silicon-based MOS devices and FinFETs, from the point of view of the direct current and of the input capacitance; the impact of the same parameters on the drain-source current of a GFET was assessed in [63]. Concerning graphene-based devices, the range of variation that should be considered for the geometrical factors is very process-dependent.…”
Section: Input Parameter Spacementioning
confidence: 99%
“…In this work, the factors chosen for the tolerance analysis are W, L, and t OX , and in the absence of an initial estimate of the process tolerances, a variation ±∆ within the 10% of the nominal value is considered for each factor, in analogy with the approach proposed in [62,63,[67][68][69].…”
Section: Input Parameter Spacementioning
confidence: 99%
“…In recent years, optical fiber devices have been widely explored in the literature for hydrostatic pressure [13], lateral load [14], and strain [15,16] sensing. They have, therefore, general application as optical sensing devices; however, thin graphene oxide (GO) [17][18][19][20][21] films have gained acceptance in the development of several devices [22][23][24][25][26][27][28][29][30][31] and sensors [32][33][34][35][36][37][38][39][40]. Recently, it has been demonstrated that hollow microsphere fiberbased sensors, conforming to Fabry-Perot interferometers (FPI), can be used in sensing applications [41] by using GO as a tunable platform to enhance the spectral features of hollow microsphere FPI fiber sensor devices.…”
Section: Introductionmentioning
confidence: 99%